Effect of moisture content variation on dielectric properties of various plant leaves at microwave frequencies - Pratipal D. Chauhan; Deepak H. Gadani; Vipin A. Rana (Scientific Reports)
Abstract Complex permittivity of Corn, Jowar, Ashoka and Banana plant leaves was measured using a Vector Network Analyzer (Anritsu Shockline Model-MS46322A) over 500 MHz to 15 GHz frequency range, at different moisture contents. The dielectric constant ( $$ε$$ ε ′) and dielectric loss ( $$ε$$ ε ″) of the leaves decrease with decrease in moisture content over this frequency range. For the leaves having moisture content less than certain critical moisture level (CML), the values of $$ε$$ ε ′ and $$ε$$ ε ” remain almost constant with frequency variation. $$ε$$ ε ″ does not increase appreciably with the increase in moisture content up to CML. CML is found to vary for different types of leaves. At higher moisture level, $$ε$$ ε ′ and $$ε$$ ε ″ exhibit frequency dependence. Above certain moisture level in the leaves, $$ε$$ ε ″ starts to increase slowly with the increase in frequency above 3 GHz approaching towards the dielectric relaxation of water. The values of $$ε$$ ε ′ and $$ε$$ ε ″ were also measured for the extract of leaves and compared with the values calculated using Stogryn equations for the same salinity, and the results agree with the calculated values. The measured values of $$ε$$ ε ′ and $$ε$$ ε ″ for the leaves were compared with the values calculated using Debye–Cole dual dispersion dielectric model and are found to match very well.